Estudo das alterações estruturais e da função diastólica cardíaca em mulheres portadoras de diabetes melito gestacional - Oliveira, Alexandra Paula de [UNESP] (2014)
Background: Gestational Diabetes Mellitus (GDM) is a risk condition for developing type 2 diabetes and its possible future developments. It is considered an independent risk factor for cardiovascular disease, the leading cause of death among diabetic patients. Objective: To identify and compare the structural and diastolic function in pregnant women with gestational diabetes mellitus and healthy pregnant women and verify possible correlation between clinical and biochemical variables with maternal ventricular mass index (LVMI) and the ratio of peak of transmitral diastolic flow velocity in early diastole (E') and peak velocity of transmitral diastolic flow during atrial contraction (A'). Subject and Methods: This was a prospective cross-sectional study in women with GDM (n = 21) and healthy pregnant women (n = 23). All the women underwent echocardiography between the 34th. and the 37th. weeks of gestation, and the results were statistically analyzed for comparison between groups, adopting the threshold of significance of 95% (p <0.05). Results: Clinical features and biochemical variables, values for age, parity, body mass index gestational and before pregnancy, fasting glucose and hemoglobin A1c were significantly higher in GDM group. Posterior wall thickness, interventricular septum, LV mass and LV mass index were significantly higher in GDM group. The E’ and E'/A' were significantly lower in the GDM group, which also showed a positive correlation between LVMI, fasting glucose and pregnancy body mass index. Conclusion: Pregnant women with GDM have different diastolic profile, near to dysfunctional pattern, but within the range of normal values for the parameters studied. Even so, as the dysfunctional pattern tends to evolve with advancing age, it is recommended to these women more rigorous monitoring of glycemic control and cardiovascular system